2009
DOI: 10.7326/0003-4819-150-9-200905050-00007
|View full text |Cite
|
Sign up to set email alerts
|

Press Releases by Academic Medical Centers: Not So Academic?

Abstract: National Cancer Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
87
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 16 publications
2
87
0
4
Order By: Relevance
“…Scientific research publications on topics related to human disease are frequently accompanied, or preceded, by a press release touting the potential cures promised by this new breakthrough. These releases -often not written by non-scientists or 'enhanced' by press offices -have been said to "promote research that has uncertain relevance to human health" and fail to "provide key facts or acknowledge important limitations" [10]. These press releases, having passed into the public domain, may then be magnified further by sensationalist media reporting.…”
Section: The Obstaclesmentioning
confidence: 99%
“…Scientific research publications on topics related to human disease are frequently accompanied, or preceded, by a press release touting the potential cures promised by this new breakthrough. These releases -often not written by non-scientists or 'enhanced' by press offices -have been said to "promote research that has uncertain relevance to human health" and fail to "provide key facts or acknowledge important limitations" [10]. These press releases, having passed into the public domain, may then be magnified further by sensationalist media reporting.…”
Section: The Obstaclesmentioning
confidence: 99%
“…While we would not dispute that the media can at times distort, simplify, and misrepresent scientific findings, it is the joint responsibility of the scientists, press offices, and the institutions that host them to ensure that the messages we put into the public domain are representative of our research and convey the messages we wish the public to receive. 7 It could be argued that more nuanced press releases might lead to less media coverage; however, Sumner et al observed that there was little evidence that exaggeration in press releases increased the uptake of news or the number of associated news stories. 4 This suggests that high profile, accurate coverage is possible, and we believe that it would be unfortunate if Ding et al's experience and commentary discouraged scientists from disseminating their findings through the media.…”
mentioning
confidence: 99%
“…Not surprisingly researchers and their institutions commonly collaborate on press releases to promote news coverage of new medical studies, and many journals issue press releases independently 4. Press releases increase the odds that a study will receive news coverage5 and influence the content of eventual press coverage 6.…”
mentioning
confidence: 99%